Carcass and Gut Characteristics of Broiler Chicken Fed Different Energy Sources - Yunusa , Y.; Doma, U.D.; Zahraddeen, D.; Umar, A.; Abubakar, S.B. (International Journal of Poultry Science, 2014)
The effect of feeding broiler chicken with different dietary energy sources on the carcass yield and gut characteristics was investigated. Five diets containing maize, red sorghum, white sorghum, Gero millet and Dauro millet were formulated and designated as 1, 2, 3, 4 and 5, respectively. Two hundred and ten day old marshal breed of broiler chicks were randomly allotted to five dietary treatments in a completely randomized design and each of the treatment was replicated three times. Feed and water were provided ad libitum and the feeding trial lasted for eight weeks. Most of the carcass and gut parameters did not differ significantly except live weight, kidney weight, plucked weight, eviscerated weight, carcass weight, kidney weight, gizzard weight (p